Ensaios sobre a vulnerabilidade socioeconômica da desertificação no semiárido brasileiro - Rodrigues, Camila Pereira Brígido (2017)
The socioeconomic character of vulnerability to desertification in the Brazilian semi-arid region has aroused the interest of scholars and alerted decision-makers to the need to understand the phenomenon more holistically. However, there are still gaps in knowledge that demand research on how vulnerability to desertification is distributed in the region, what factors contribute most to the problem, what changes have been observed in recent years and areas most affected. In this context, the objective of the research is to analyze the socioeconomic vulnerability to desertification in the municipalities of the Brazilian semi-arid region from 2000 to 2010. For this purpose, a system of indicators of socioeconomic vulnerability at the municipal level was developed, capable of being fed with Temporal and secondary data. The Brazilian Institute of Geography and Research (IBGE), the National Semiarid Institute (INSA) and the United Nations Development Program (UNDP) were used as data sources. Then, a factorial analysis model was used to identify the factors that explain the vulnerability and obtaining weights for the construction of a Socioeconomic Vulnerability Index to Desertification (IVSD). Finally, a cluster analysis was performed to classify the municipalities. The main results showed that there was a reduction in the socioeconomic vulnerability to desertification in the Brazilian semi-arid region (SAB) between 2000 and 2010. In addition, the explanatory factors of this vulnerability also changed during the period. In 2000, were Poverty and Education, while in 2010 were Economic and Population Growth. The mapping of the IVSD allowed the identification of the areas with the greatest vulnerability. These areas were not necessarily coincident with officially recognized desertification nuclei, which were defined from local physical and natural characteristics. This result is relevant and highlights that socioeconomic vulnerability to desertification is primarily the result of anthropogenic actions and therefore is present throughout the semi-arid as a threat to local ecosystems, especially those inserted in rural areas.